Committed to the state asylum : insanity and society in nineteenth-century Quebec and Ontario - Moran, James E. (McGill-Queen's/Associated Medical Services (Hannah Institute) studies in the history of medicine, health, and society, 2000)
"Committed to the State Asylum examines the evolution of the asylum as the response to insanity in nineteenth-century Quebec and Ontario. Focusing on the creation and development of government-funded asylums for the insane - among the largest and most important nineteenth-century institutions in both provinces - James Moran argues that asylum development was the result of complex relationships among a wide array of people, including state inspectors and administrators, asylum doctors, local magistrates, jail surgeons, religious authorities, and the relatives and neighbours of those who were considered to be insane." "Unlike other studies, Committed to the State Asylum shows the important role that the community played in shaping the asylum and tackles the thorny issue of state development, explaining how state asylums developed differently in each province. Moran considers Canada's pioneering institutional efforts at dealing with the criminally insane and why those efforts lasted only a short time, shedding new light on the debate about the nature and extent of state involvement in nineteenth-century Canadian society." "Committed to the State Asylum offers new insights into the ways in which both ordinary families and the state understood and responded to those they thought had crossed the boundaries of sane behaviour."--Jacket